Dialectics of Place and Space in Forster's A Passage to India: A Lacanian Reading - Ercan Tugay Akı (Ideas: Journal of English Literary Studies)
This study provides a reading of Forster’s A Passage to India in terms of space from the vantage point of Lacanian psychoanalysis in order to show that the novel fictionalises the dialectics of the place and space and its implications for the British and to argue that the attempt of ideological and semantic appropriation of India by the British ultimately fails and results in an ironical entrapment of the British in the places they created in the midst of the Indian space except for Adela who manages to cope with India without turning it into a place from a space. Topography functions as a semantic ground in the novel, and the way that the topographical elements are viewed by the Westerners reveals how they commit epistemic violence by refusing to acknowledge the Symbolic patterns of the non-West. In the context of providing such a Lacanian psychoanalytic analysis of the novel with a particular focus on the topography, the Marabar Caves, intersubjectivity, and the gaze of the other; the paper will borrow such terms as the unconscious, the Symbolic, talking cure/full speech, and object of desire from Lacan.